Quaternary dinocysts produced by dinoflagellate mobile cells potentially toxic deposited at the medial slope from the Albacora region of Campos Basin RJ/Brazil - Souza, Jaqueline Torres de; Mendonça Filho, João Graciano; Oliveira, Antonio Donizeti de; Menezes, Mariângela (Anuário do Instituto de Geociências, 2007)
Abstract